Phenomenological perspectives on plurality - Heiden, Gerrit Jan van der, 1976- (Studies in Contemporary Phenomenology, 2015)
Phenomenological Perspectives on Plurality offers twelve essays that discuss how the question of plurality is thought in contemporary continental philosophy. In particular, its essays investigate how this issue influences topics in ontology, aesthetics, and social and political philosophy as well as other fields. In the wake of the critique of metaphysics as onto-theology, the question of plurality has become a central focus of philosophy today. This question does not only give rise to rethink the beginning of metaphysics as well as some of its basic concepts, such as the notion of God, but also influences the contemporary conception of art, identity and community.